FORMULASI DAN UJI AKTIVITAS SEDIAAN CLAY MASK DARI EKSTRAK KULIT PEPAYA (CARICA PAPAYA LINN.) DENGAN KOMBINASI EKSTRAK KULIT LEMON (CITRUS LIMON BURM F.) SEBAGAI ANTI AGING - Patimah, Kusnul; Hidayati, Evi Nurul; Santoso, Joko (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Aging is a change in humans caused by age, psychological and social factors. based on a patient survey at rsud dr. soetomo surabaya in 2017, the group diagnosed with photoaging caused by sun exposure had a prevalence rate of 50.27%. papaya peel and lemon peel contain vitamin c and flavonoids that have properties as natural antioxidants. clay mask preparations are able to remove dirt on the face so that the skin becomes brighter and cleaner. the purpose of this research is to determine the activity and physical quality of the clay mask preparation formulation of papaya fruit peel extract (carica papaya linn.) and lemon peel extract (citrus limon burm f.) as anti-aging. the method in this study is an experimental method with a design in the form of a true experimental post test only control group design. the results of this study obtained the ic50 value of papaya peel extract with a dose of 2 grams of 51.88 ppm and lemon peel extract with a dose of 5 grams of 39.87 ppm, evaluation of clay mask preparations fi obtained brown preparations, homogeneous preparations, ph 5.44, drying time 15.25 minutes; fii obtained brown preparations, homogeneous preparations, ph 5.66, drying time 5.44 minutes; fiii obtained brown preparations, homogeneous preparations, ph 5.50, drying time 20.26 minutes. the conclusion of this study is that papaya peel extract and lemon peel extract have antioxidant activity as anti-aging, the physical quality of clay mask preparations of all formulations has met the standards and the most stable formula is fii. the most preferred formula by volunteers is fii and all formulations do not cause irritation.